Free energy calculations in biomolecule-nanomaterial interactions - Fu, Hongze; Zhu, Yinbang; Chen, Qu (Frontiers in Physics, 2024)
In computational chemistry and molecular modeling, the interactions between biomolecules (BMs) and nanomaterials (NMs) play a crucial role in various physical and biological processes, and have significant implications in material discovery and development. While there is extensive literature on free energy calculations for drugtarget interactions, reviews specifically addressing BM-NM interactions are relatively scarce. This manuscript aims to fill in this gap by presenting a comprehensive overview of the most widely used and well-established methods for free energy calculations. It provides a detailed analysis of the advantages and limitations of these methods and discusses their applicability to BM-NM systems. This work is intended to offer insights into free energy calculations and serve as a guide for future research in this field.